2022
DOI: 10.1155/2022/7892397
|View full text |Cite
|
Sign up to set email alerts
|

Potential Material Basis of Yupingfeng Powder for the Prevention and Treatment of 2019 Novel Coronavirus Pneumonia: A Study Involving Molecular Docking and Molecular Dynamic Simulation Technology

Abstract: Objective. In this study, we investigated the potential material basis of Yupingfeng powder in the prevention and treatment of 2019 novel coronavirus pneumonia (NCP) by applying molecular docking and molecular dynamic simulation technology. Design. The active ingredients and predictive targets of Yupingfeng powder were sourced using the TCMSP, ETCM, and TCMIP traditional Chinese medicine databases. NCP-related targets were then acquired from the DisGeNET and GeneCards databases, and common disease-drug targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Several studies shed light on the primary therapeutic effect of Yupingfeng Powder and its effectiveness in improving the barrier function of the airway mucosa. This is accomplished by restoring and safeguarding the airway mucosa’s natural outcomes and controlling the body’s immunological function ( Gao et al, 2009 ; Wang et al, 2022 ; Yu et al, 2022 ). Contemporary pharmacology has demonstrated that Forsythia suspensa (Thunb.)…”
Section: Discussionmentioning
confidence: 99%
“…Several studies shed light on the primary therapeutic effect of Yupingfeng Powder and its effectiveness in improving the barrier function of the airway mucosa. This is accomplished by restoring and safeguarding the airway mucosa’s natural outcomes and controlling the body’s immunological function ( Gao et al, 2009 ; Wang et al, 2022 ; Yu et al, 2022 ). Contemporary pharmacology has demonstrated that Forsythia suspensa (Thunb.)…”
Section: Discussionmentioning
confidence: 99%
“…3 Recently, YPFG has been used in treating and preventing COVID-19. [4][5][6] The biological activities of flavonoids and saponins from A. membranaceus (Fisch.) Bunge and chromones from S. divaricata (Turcz.)…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly used to prevent infectious diseases such as colds, pneumonia, 2 and rhinitis 3 . Recently, YPFG has been used in treating and preventing COVID‐19 4–6 . The biological activities of flavonoids and saponins from A. membranaceus (Fisch.)…”
Section: Introductionmentioning
confidence: 99%